Anesthesia for a Pediatric Patient with Cardiofaciocutaneous Syndrome. (1st April 2015) - Lam, Humphrey; Dare, Shannon; Nguyen, Thanh; Austin, Thomas
Abstract : Cardiofaciocutaneous syndrome is a rare syndrome that is characterized by distinct craniofacial features, cardiac abnormalities, and multiple organ involvement. Patients may present with pulmonary stenosis, hypertrophic cardiomyopathy, micrognathia, a short neck, laryngomalacia, and tracheomalacia; all of which may significantly impact the perioperative course of these patients. We describe a 6-year-old child with cardiofaciocutaneous syndrome presenting for an orthopedic procedure. He had an uneventful perioperative and postoperative course.